Training Up: Effectiveness of Collaborative Experiential Learning workshops to improve faculty confidence in course design principles - Krejci, Sarah (Experiential Learning and Teaching in Higher Education, 2025)
While faculty are subject matter experts in their fields of research, they are often lacking the pedagogical training to support student academic success. Additionally, career readiness skills are increasingly a focus in higher education through the intentional inclusion of soft skills or "21st-century skills" in the classroom. Experiential learning theory is an established framework to enhance student learning and switch from passive learning modalities to active learning in the classroom and can serve as a support for students' development of workforce readiness skills while learning course content. Bethune-Cookman University is engaged in a five-year initiative to improve student academic success through experiential learning. Faculty workshops were developed to assist faculty with reimagining their undergraduate courses with ELT and incorporating lessons designed to improve students' transferable competencies and skills. Faculty surveys demonstrate increases in confidence and knowledge in applying ELT principles within their course designs at the conclusion of the workshops. The course planning document developed for this workshop series facilitated the faculty's application of ELT and course design principles to 32 reimagined courses across the University and from first-year through graduate courses.